The Penang citizens' intention to use the proposed Bayan Lepas LRT in Penang Island - Cheng, Sing Yang; Yap, Hui Min; Tan, Yi Wen; Zainuddin, Nizamuddin (2017)
With the increased of the population of Penang citizens, there is a need to have adequate modes of transportation to fulfill the citizens’ mobility.However, with the small surface area of Penang Island, the traffic congestion happened, especially during the peak hour, weekends and public holidays.Thus, in order to deal with the worsening traffic congestion problem over the Penang Island, the very first line of Bayan Lepas LRT project has been proposed under the Penang Transport Master Plan (PTMP).But, regarding the installation of LRT, there are more bad comments than good comments about the project cost, land use and so on.Here, the perception of Penang citizens toward the services provided by the public transportation is an important indicator to identify the Penang citizens’ intention to use the proposed Bayan Lepas LRT.The theory of Technology Acceptance Model (TAM) (Sumaedi, Bakti, Rakhmawati, Astrini, Widianti, & Yarmen (2016) is adopted and being extended to cover that limitation of original TAM with an additional variable of perceived value as the based theory of this research.A good experience on the previous ride of public transportation will definitely leave with a good impression.That will encourage the citizens to use the public transportation again like proposed Bayan Lepas LRT.Thus, this study aims to identify the Penang citizens’ intention to use the proposed Bayan Lepas LRT in Penang Island.The predictor variables (Perceived usefulness, Perceived ease-of-use, Perceived value) and the criterion variable (The intention of Penang citizens to use Bayan Lepas LRT) are involved in the study.A non-probability sampling method was used to obtain the data from 390 respondents that are currently staying either in Penang Island or Penang Mainland.The findings will look into the correlation of all of the variables involved in the study.